Neuropsychological assessment in patients with relapsing-remitting multiple sclerosis and mild functional impairment: correlation with magnetic resonance imaging. Issue 2 (February 1990) - Anzola, G P; Bevilacqua, L; Cappa, S F; Capra, R; Faglia, L; Farina, E; Frisoni, G; Mariani, C; Pasolini, M P; Vignolo, L A
Abstract : Forty one moderately impaired patients with clinically confirmed multiple sclerosis (MS) and a relapsing-remitting course were submitted to a neuropsychological battery and magnetic resonance imaging (MRI) to correlate the neuropsychological performances with the degree of cerebral demyelination. The neuropsychological results were indicative of a very mild overall impairment. The patients were subdivided into two groups (extensive periventricular demyelination or discrete lesions on MRI) and the results of neuropsychological tests compared. Patients with extensive periventricular demyelination had an inferior performance on concept formation, non-verbal reasoning and verbal memory tests.